(3GdQhVI GdHgjI aj TQM GddeYI GdOeTbjIs - (3GdYGedj, GdLYHj, YR GdOjf, Rjf GdOjf Hf Ydj Hf CMeO, J (B966(3g`s ((3NOG hjQOj Hf EdjGS Nhjs)
(3ChdgG (B:s
(3GdeDLQ hGdeSJCLQ EdG Cf jchf GdYjf ehbhaI Ydi GdeLQ hYdi ef HYOg ef GdHWhf (B...s
(3BNQgG (B:s
(3hgh eTcd Ydi EWdGbg aEf eLQO hbhYg CYe ef JaQjWge ajg Hd ef JaQjW GdYGbd hef Ke ChQOgG (B...(3djcf gPG BNQ GddeYI(B... (3hfaY HTQMg ceG faY HCUdg (B...s
(3JHUQI GdeDda (B:s
(3GdTgjQ HGdTgjO GdKGfjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B3(3, U(B64s
(3GdPQjYI, HQbe(B: 1757s
(3EjVGM Gdecfhf(B: (3L(B1(3, (B593s
Keywords: (3abg GdePGgH GdCNQis